Записки коменданта Московского Кремля - Мальков Павел Дмитриевич (Молодая гвардия, 1962)
Экземпляры: КХ (20190312) / Инвентарный номер: 313652 / Сис.шифр: 9(С)21 / Авт.знак: М 21 / ГРНТИ: 03 / ББК: 63